Soil microbiome dysbiosis and rhizosphere metabolic dysfunction drive continuous cropping obstacles of Codonopsis tangshen - Xu, Dabing; Peng, Chenglin; Si, Guohan; Xu, Xiangyu; Zhao, Shujun; You, Chuan; Zhou, Wuxian (Frontiers in Microbiology, 2025)
Successive monocropping of Codonopsis tangshen causes continuous cropping obstacles, impairing growth, yield, and quality. To investigate the soil environmental and microbial changes caused by these obstacles, we collected both continuous cropping (C-crop) and non-continuous cropping (NC-crop) soil for analysis. We employed high-throughput sequencing, Biolog-ECO microplate, and metabolomics technology to evaluate microbial diversity, community structure, and carbon source utilization efficiency. Compared with NC-crop, C-crop decreased the yield and polysaccharide content of C. tangshen by 40.47 and 29.4%, respectively. Continuous cropping significantly altered soil physicochemical properties and metabolomes, driving distinct shifts in microbial community structure and impairing carbon utilization efficiency. Microbial carbon use efficiency was positively correlated with key soil bacteria and fungi. However, their abundance decreased significantly under continuous cropping, ultimately disrupting soil carbon cycling. Moreover, key bacterial (e.g., Flavobacterium, Lysobacter, Pseudomonas, Burkholderia) and fungal genera (e.g., Ophiosphaerella, Dactylonectria, Humicola) showed strong correlations with critical soil physicochemical properties, microbial carbohydrate metabolism, and rhizosphere metabolite profiles. The reduced abundance of these microbes disrupted soil nutrient balance and microbial activity, potentially contributing to C. tangshen continuous cropping obstacles. This study contributes to the understanding of the mechanisms underlying continuous cropping obstacles in C. tangshen and lays the foundation for developing strategies to alleviate these obstacles.